Implementation of Kaplan Type Ducted Propeller on Hydrodynamics of Offshore Supply Vessel (OSV) - Sakti, Gedhe Angkoso Nur Sofa Sakti; Winarno, Arif (International Journal of Marine Engineering Innovation and Research, 2024)
When operating at sea, a reliable ship must meet the planned service speed using a propulsion system. One type of propulsion system used is a ducted propeller, which is a type of propeller equipped with a channel in the form of a foil that surrounds the propeller to form a tube (nozzle). This nozzle has the ability to increase the value of thrust and torque, so that its application can increase thrust and torque compared to a propeller without a nozzle. This study aims to determine the application of the kort nozzle with MARIN foil nozzle types 19A, 22, 24 on the Ka-40 propeller on the Offshore Supply Vessel (OSV) ship using the Computational Fluid Dynamic (CFD) method. This study obtained results from all models with the model with the highest thrust force is the 19A nozzle model with a value of 367,413.41 N, while the model with the lowest thrust force is model 24 with a value of 356,314.9 Nm. From these results, it can be concluded that the relationship between the length of the kort nozzle and the thrust force is inversely proportional, that is, the greater the length of the kort nozzle used, the smaller the thrust force value produced. Likewise, the relationship between the length of the kort nozzle with torque is also inversely proportional, that is, the greater the length of the kort nozzle used, the smaller the torque value produced.